IBN RAḤĪQ'S TEXT ON THE MILKY WAY: PERCEPTION OF THE MILKY WAY IN THE EARLY ISLAMIC SOCIETY. Issue 2 (September 2019) - Eckart, Andreas
Abstract: Ibn Raḥīq is an 11th century scholar who compiled a book on popular astronomy. This work included a section in which he summarizes basic knowledge of the Milky Way as it was wide spread in the first centuries after the hejira. Ibn Raḥīq gives a comprehensive overview of the perception of the Milky Way that reaches from its use as a test for knowledge of the religious tradition and for agricultural purposes on the one hand to an exact astronomical description of its shape in the sky during the year and to theories of its nature and composition on the other hand. We use a comparison of his text to those of Ibn al-Haytham and others to investigate the role the Milky Way played in early Islamic civilization from its beginning until the 15th century. Résumé: Ibn Raḥīq est un érudit duxi e siècle qui a compilé un livre sur l'astronomie grand public. Ce travail comprenait une section dans laquelle il résumait les connaissances de base sur la Voie lactée, telle qu'elle prévalait dans les premiers siècles après l'Hégire. Ibn Raḥīq donne un aperçu complet de la perception de la Voie lactée, allant de son utilisation comme test pour la connaissance de la tradition religieuse et de ses applications agricoles jusqu'à une description astronomique exacte de sa forme dans le ciel au cours de l'année et à des théories sur sa nature et sa composition. Nous utilisons une comparaison de son texte avec ceux d'Ibn al-Haytham et d'autres auteurs pour étudier le rôle de la Voie lactée dans la civilisation islamique depuis le début de son existence jusqu'auxv e siècle.